UV-Enhanced NaClO Oxidation of Nitric Oxide from Simulated Flue Gas - Shao-long Yang; Zhi-tao Han; Jing-ming Dong; Zi-sheng Zheng; Xin-xiang Pan (Journal of Chemistry)
A wet de-NOx technique based on an UV-enhanced NaClO oxidation process was investigated for simulated flue gas of a diesel engine using a bench-scale reaction chamber. The effects of UV irradiation time, initial pH value, and available chlorine concentration of NaClO solution were studied, respectively. The results showed that when the UV irradiation time was 17.5 min and the initial pH value of NaClO solution was 6, NO removal efficiency of UV/NaClO solution was increased by 19.6% compared with that of NaClO solution. Meanwhile, when the available chlorine concentration of NaClO solution decreased from 0.1 wt% to 0.05 wt%, the enhancement in NO removal efficiency of UV/NaClO solution increased from 19.6% to 24%, compared with that of NaClO solution. The reaction pathways of NaClO solution photolysis and NO removal by UV/NaClO process were preliminarily discussed. The results suggested that HOCl might be the most active species that released many UV-induced photooxidants through photolysis reactions, which played an important role in NO removal process.